2012
DOI: 10.1159/000342633
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Lactoferrin Attenuates Intestinal Ischemia-Reperfusion Injury in Rats

Abstract: Background: Intestinal ischemia-reperfusion (I/R) is a common and serious clinical condition. Lactoferrin (Lf) has displayed antioxidative and anti-inflammatory activities in protecting the intestinal mucosa. The objective of this study was to investigate whether oral administration of Lf could attenuate I/R-induced intestinal injury. Methods: The experimental design consisted of three groups of Wistar rats (24 per group): sham operation, control (I/R, saline), Lf (I/R, Lf). Intestinal I/R was produced by occl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…LTF is an iron-binding glycoprotein and involved in several biological functions, including iron absorption, antioxidative activities, and regulating the systemic immune response [24]. The present study showed that LTF is significantly down-regulated in CMECs during I/R, similar to a previous study [25]. According to the classical research of Ambrosio [26], the no-reflow area has a large number of neutrophils and substantial platelet aggregation, which may be the main cause of capillary vessel embolism.…”
Section: Discussionsupporting
confidence: 90%
“…LTF is an iron-binding glycoprotein and involved in several biological functions, including iron absorption, antioxidative activities, and regulating the systemic immune response [24]. The present study showed that LTF is significantly down-regulated in CMECs during I/R, similar to a previous study [25]. According to the classical research of Ambrosio [26], the no-reflow area has a large number of neutrophils and substantial platelet aggregation, which may be the main cause of capillary vessel embolism.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, oral LF administration reduces intestinal ischemia-reperfusion injury through antioxidative, anti-inflammatory, and antiapoptotic actions in rats. 28 Thus, LF has the potential to promote angiogenesis and is effective for revascularization in response to ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…However, when the degree and duration of gut hypoperfusion are severe, gut reperfusion may instead worsen remote organ injury by excessively activating polymorphonuclear neutrophils, oxidative stress, and proinflammatory mediators [1][2][3][4][5]. Various therapies have been proposed for reducing gut ischemia reperfusion (I/R) injury [6][7][8][9]. glycine) synthesized from glutamic acid, cysteine, and glycine, is a major systemic antioxidant.…”
Section: Introductionmentioning
confidence: 99%